Teacher well-being: Investigating the contributions of school climate and job crafting - Benjamin Dreer (Cogent Education, 2022)
Teachers’ well-being is important for the optimal functioning of schools and educational systems. Contextual and individual factors influencing teachers’ work-related well-being have been identified but rarely investigated concurrently. This study examined contributions of school climate and job crafting to teacher well-being. Time-lagged survey data from 564 German teachers was analysed. The hypothesised model whereby school climate and job crafting were separate predictors of well-being fitted the data well. Analyses further revealed that the effect of school climate and job crafting is additive. Teachers who reported the highest rates of school climate and the highest scores in job crafting experienced the highest well-being. Results of this study highlight the importance of both school climate and job crafting for supporting teacher well-being.